2011
DOI: 10.3109/14767058.2011.622002
|View full text |Cite
|
Sign up to set email alerts
|

TORCH screening in polyhydramnios: an observational study

Abstract: While the sample size of this study is small to disregard the significance of TORCH test in polyhydramnios, the statistical evaluation shows that this test is not beneficial in women in whom polyhydramnios is an isolated ultrasound finding, especially when it is diagnosed in third trimester.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 12 publications
1
16
0
1
Order By: Relevance
“…Rubella is screened for as part of the routine antenatal screen. Our findings have further confirmed the targeted approach to serology screening 4 . We therefore now only perform CMV serology unless there is an overwhelming clinical indication for the addition of toxoplasma testing.…”
supporting
confidence: 76%
“…Rubella is screened for as part of the routine antenatal screen. Our findings have further confirmed the targeted approach to serology screening 4 . We therefore now only perform CMV serology unless there is an overwhelming clinical indication for the addition of toxoplasma testing.…”
supporting
confidence: 76%
“…TORCH infections may also be associated with polyhydramnios [22,23]. Still, the relevance of routine TORCH serology in affected pregnancies has been under debate [27,40,41]. In our population 2.9 % of patients with polyhydramnios had a recent infection, with the overwhelming number being caused by CMV and parvovirus B19.…”
Section: Comment !mentioning
confidence: 87%
“…Our results are in agreement with the study by Fayyaz et al , which showed that the TORCH test is not beneficial in women in whom polyhydramnios is an isolated ultrasound finding, especially when it is diagnosed in the third trimester. Similarly, Abdel Fattah et al , after reviewing the indication and value of 462 TORCH testing requested for fetal reasons during a 10‐year period, found that no cases of fetal/maternal infection were associated with polyhydramnios.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of oligohydramnios in cases of confirmed CMV infection is reported to be 25%, and it can be explained by the affinity of the virus for the fetal kidneys . The need for TORCH screening in cases of polyhydramnios is therefore currently the object of much debate . The aim of this study was to evaluate the rate of positive infectious disease testing among a cohort of women diagnosed with polyhydramnios in a tertiary care setting.…”
Section: Introductionmentioning
confidence: 99%